Dynamic Metasomatism: Stable Isotopes, Fluid Evolution, and Deformation of Albitite and Scapolite Metagabbro (Bamble Lithotectonic Domain, South Norway). (17th January 2018) - Engvik, Ane K.; Taubald, Heinrich; Solli, Arne; Grenne, Tor; Austrheim, Håkon
Abstract : New stable isotopic data from mineral separates of albite, scapolite, amphibole, quartz, and calcite of metasomatic rocks (Bamble lithotectonic domain) give increased knowledge on fluid type, source, and evolution during metamorphism. Albite from a variety of albitites gives δ 18 O S M O W values of 5.1–11.1‰, while quartz from clinopyroxene-bearing albitite gives 11.5–11.6‰ . δ 18 O S M O W values for calcite samples varies between 3.4 and 12.4‰ and shows more consistent δ 13 C values of −4.6 to- 6.0 ‰ . Amphibole from scapolite metagabbro yields a δ 18 O S M O W value of 4.3 to 6.7‰ and δ D S M O W value of −84 to −50‰, while the scapolite gives δ 18 O S M O W values in the range of 7.4 to10.6 ‰ . These results support the interpretation that the original magmatic rocks were metasomatised by seawater solutions with a possible involvement from magmatic fluids. Scapolitisation and albitisation led to contrasting chemical evolution with respect to elements like P, Ti, V, Fe, and halogens. The halogens deposited as Cl-scapolite were dissolved by albitisation fluid and reused as a ligand for metal transport. Many of the metal deposits in the Bamble lithotectonic domain, including Fe-ores, rutile, and apatite deposits formed during metasomatism. Brittle to ductile deformation concurrent with metasomatic infiltration illustrates the dynamics and importance of metasomatic processes during crustal evolution.